Unlocking Dual Functionality in Triazine‐Based Emitters: Synergistic Enhancement of Two‐Photon Absorption and TADF‐OLED Performance with Electron‐Withdrawing Substituents - Chitose, Youhei; Mageswari, Gomathi Vinayakam; Zenke, Ryota; Ide, Toshiharu; Kohata, Shintaro; Lin, Ja‐Hon; Lin, Tzu‐Chau; Tsuchiya, Youichi; Adachi, Chihaya (Advanced materials (Weinheim), 2025)
The simultaneous realization of two‐photon absorption (2PA) and thermally activated delayed fluorescence (TADF) in a single molecular system remains challenging due to an inherent trade‐off in their molecular design requirements. In this study, we present a strategy to enhance both properties by introducing electron‐withdrawing substituents into the CzTRZ scaffold, thereby leveraging an electron‐withdrawing‐enhanced intramolecular charge transfer (EWICT) character. The incorporation of TRZCF 3 and TRZCN units effectively enhances the charge transfer (CT) character of CzTRZ, resulting in high 2PA cross‐sections (156 GM for CzTRZCF 3 and 200 GM for CzTRZCN ) and a reduced singlet‐triplet energy gap (Δ E ST = E S1 – E T1 ). Computational and experimental studies reveal that incorporating TRZCF 3 and TRZCN units selectively stabilizes the S 1 state and reduces Δ E ST , significantly facilitating the reversed intersystem crossing (RISC) process. Notably, 1c exhibits the fastest RISC rate ( k RISC ), leading to superior TADF properties and an external quantum efficiency (EQE) of 13.5% in OLEDs. Moreover, a relatively high two‐photon brightness of 174 GM is estimated for 1c . These findings demonstrate a rational molecular design strategy for the synergistic enhancement of 2PA cross‐sections and excellent OLED performance, paving the way for applications in advanced imaging probes and organic semiconductors.